2008
DOI: 10.1007/s10714-008-0622-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiating gravitational collapse with shear viscosity revisited

Abstract: A new model is proposed to a collapsing radiating star consisting of an isotropic fluid with shear viscosity undergoing radial heat flow with outgoing radiation. In a previous paper we have introduced a function time dependent into the g rr , besides the time dependent metric functions g θθ and g φφ . The aim of this work is to generalize this previous model by introducing shear viscosity and compare it to the non-viscous collapse. The behavior of the density, pressure, mass, luminosity and the effective adiab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 30 publications
1
60
0
Order By: Relevance
“…A generic study has shown that a contracting body on its way to continued collapse must tend to be radiation pressure dominated (Mitra 2006c). Several studies have also suggested that the contracting body may even radiate out its entire mass energy to avoid formation of trapped surfaces or horizons (Chan 2003;Fayos and Torres 2008;Pinheiro and Chan 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A generic study has shown that a contracting body on its way to continued collapse must tend to be radiation pressure dominated (Mitra 2006c). Several studies have also suggested that the contracting body may even radiate out its entire mass energy to avoid formation of trapped surfaces or horizons (Chan 2003;Fayos and Torres 2008;Pinheiro and Chan 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, (14) also suggests that given a form for the density, we can determine both the magnitude and the sign of the pressure. The sign of the pressure is crucial as it reveals more about the nature of the null fluid and the interaction of the fluid with the gravitational field.…”
Section: Qualitative Features Of the Exterior Null Fluidmentioning
confidence: 99%
“…The influence of pressure anisotropy, shear and bulk viscosity on the density, mass, luminosity and effective adiabatic index of an 8M contracting radiating star was studied by Chan [12,13]. These results were later extended by Pinheiro and Chan [14]. Misthry et al [15] generated nonlinear exact models in the shear-free regime for relativistic stars with heat flow, using a group theoretic approach that involves the Lie symmetry analysis of the Santos junction condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a trapped surface or EH, such objects must keep on radiating and contracting even if at infinitesimally slow rate. In fact there are several GTR special solutions for physical gravitational collapse which suggest that effect of radiation pressure and dissipation may cause formation of hot radiating ultra-compact objects rather that any BH or naked singularity [34,35]. Radiation pressure apart, generation of tangential pressure too can arrest the continued collapse.…”
Section: Gravitational Collapsementioning
confidence: 99%